Modified lithium metal electrode, preparation method and application thereof, and lithium ion battery containing modified lithium metal electrode

By forming an interface film containing lithium chloride and lithium nitride on the surface of the lithium metal electrode, the dendrites growth and safety accidents caused by the instability of the interface film of the lithium metal battery are solved, and the high cycle stability and safety performance of the battery are achieved.

CN119812212AActive Publication Date: 2025-04-11SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411998031.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Due to its high activity, lithium metal batteries are prone to side reactions with electrolytes, resulting in unstable surface interface masks, which in turn leads to dendrite growth, volume expansion, battery short circuits and safety accidents. Traditional additives are difficult to meet the stability and high ionic conductivity requirements of interface masks at the same time.

Method used

Chemical vapor deposition method was used to prepare lithium metal electrodes with surface interface films rich in lithium chloride and lithium nitride. By optimizing the content of Cl and N elements and the thickness of the interface film, the stability and ionic conductivity of the interface film were improved.

Benefits of technology

The formation and growth of lithium dendrites are significantly inhibited, the cycle stability and safety performance of the battery are improved, and the compatibility between lithium metal electrodes and ether electrolytes is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812212A_ABST
    Figure CN119812212A_ABST
Patent Text Reader

Abstract

The invention provides a modified lithium metal electrode, a preparation method and application thereof, and a lithium ion battery containing the modified lithium metal electrode. The modified lithium metal electrode comprises lithium metal and a surface interface film attached to the surface of the lithium metal, the surface interface film contains lithium chloride and lithium nitride; in the modified lithium metal electrode, the content of Cl element is 0.4%-0.8%, and the content of N element is 0.4%-0.8%. The modified lithium metal electrode comprises a surface interface film containing lithium chloride and lithium nitride, has high compatibility with an ether electrolyte, has high electronic insulativity, low ion diffusion barrier and excellent mechanical stability, remarkably inhibits formation and growth of lithium dendrites, and has the advantages of low cost and high efficiency when being used for a lithium ion battery. And the cycling stability and the safety performance of the battery are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a modified lithium metal electrode, a preparation method and application thereof, and a lithium ion battery containing the modified lithium metal electrode. Background Art

[0002] In the past three decades, lithium-ion batteries have been widely used in portable electronic devices, aerospace, grid energy storage, and new energy electric vehicles due to their good cycle stability and safety. However, after years of research, scientists have found that traditional graphite negative electrode materials have reached their theoretical capacity limit and can no longer meet people's demand for higher energy density of batteries. Lithium metal is considered to be the ultimate negative electrode choice in high-performance lithium batteries due to its ultra-high theoretical specific capacity (3860mAh / g) and lowest electrode potential (-3.04V vs. standard hydrogen electrode). However, due to its high activity, lithium metal is prone to side reactions with electrolytes, producing unstable interfacial films, resulting in ultra-high volume expansion and uncontrollable dendrite growth. The continuous growth of dendrites will pierce the diaphragm, causing the battery to short-circuit, thermal runaway, and then fire and explosion accidents.

[0003] The lithium metal interface film connects the electrolyte and lithium metal. The ionic conductivity and stability of the interface film directly determine the cycle stability and safety of lithium metal batteries. Therefore, preparing an artificial interface film with high ionic conductivity and high stability is an effective way to accelerate the commercialization of lithium metal batteries. Studies have shown that lithium chloride (LiCl) has high electronic insulation and low ion diffusion barrier. As a component of the interface film, it can effectively reduce the interface resistance and increase the ion transfer rate; lithium nitride (Li3N) has excellent mechanical stability. As a component of the interface film, it can effectively improve the ability of the interface film to inhibit the growth of lithium dendrites and improve the cycle stability of the battery. At present, researchers have introduced additives into the electrolyte to construct an interface film. However, electrolyte additives have a higher reduction potential, which is not conducive to the formation of a stable interface film. In addition, a single additive cannot simultaneously meet the needs of multi-component interface film construction.

[0004] In order to solve the problem of dendrite growth in lithium metal batteries and improve battery cycle stability and safety, the present invention uses chemical vapor deposition to prepare a lithium metal electrode rich in lithium chloride and lithium nitride surface interface film. The developed lithium metal electrode shows high compatibility with ether electrolytes and exhibits better electrochemical properties. The present invention is a promising way to solve the technical barriers to the preparation of advanced lithium metal electrodes and promote the practical application of lithium metal batteries. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defects of the prior art that lithium metal batteries are prone to side reactions with electrolytes due to their high activity, resulting in unstable surface interface films, which in turn cause dendrite growth, volume expansion, battery short circuits and safety accidents, and that traditional additives are difficult to simultaneously meet the requirements of stability of the surface interface film and high ionic conductivity, and provide a modified lithium metal electrode and its preparation method and application, and a lithium ion battery containing it. The modified lithium metal electrode of the present invention comprises a surface interface film containing lithium chloride and lithium nitride, is highly compatible with ether electrolytes, has high electronic insulation, low ion diffusion barriers and excellent mechanical stability, significantly inhibits the formation and growth of lithium dendrites, and when used in lithium ion batteries, effectively improves the cycle stability and safety performance of the battery. The preparation method of the modified lithium metal electrode of the present invention has a simple process, easy-to-control reaction conditions, cheap and easily available raw materials, can be put into actual production, and has a strong practical application prospect.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a modified lithium metal electrode, wherein the modified lithium metal electrode comprises the lithium metal and a surface interface film attached to the surface of the lithium metal;

[0008] The surface interface film contains lithium chloride and lithium nitride;

[0009] In the modified lithium metal electrode, the content of Cl element is 0.4%-0.8%, where % is the percentage of the mass of Cl element to the total mass of the modified lithium metal electrode;

[0010] In the modified lithium metal electrode, the content of N element is 0.4%-0.8%, where % is the percentage of the mass of N element to the total mass of the modified lithium metal electrode.

[0011] In this scheme, the selection of the Cl element content and the N element content optimizes the stability and ionic conductivity of the surface interface film, thereby playing a key role in improving the battery cycle stability and inhibiting the growth of lithium dendrites.

[0012] Preferably, the surface interface film has a thickness of 1 μm-100 μm.

[0013] More preferably, the surface interface film has a thickness of 1 μm-4 μm.

[0014] In this solution, the thickness of the surface interface film ensures that the surface interface film can effectively protect the lithium metal electrode while still maintaining good ionic conductivity. A thinner surface interface film helps to improve the electrochemical performance of the battery and reduce the internal resistance of the battery.

[0015] Preferably, the content of Cl element is 0.7%-0.8%.

[0016] Preferably, the content of the N element is 0.5%-0.6%.

[0017] Preferably, the lithium metal is lithium foil.

[0018] Preferably, the thickness of the lithium metal is 195 μm-499 μm, more preferably 295 μm-399 μm, for example 296 μm.

[0019] Preferably, the surface interface film also contains lithium oxide and lithium carbonate.

[0020] The present invention also provides a method for preparing a modified lithium metal electrode, characterized in that it comprises the following steps: under the protection of an inert gas, placing ammonium chloride powder and lithium metal at the lower and upper parts of a reaction container respectively without contacting each other, and preparing the modified lithium metal electrode by a chemical vapor deposition method;

[0021] The distance between the lithium metal and the ammonium chloride powder is ≤5 cm;

[0022] The temperature of the chemical vapor deposition is ≥100°C.

[0023] Preferably, the reaction container is a crucible.

[0024] Preferably, the reaction vessel is supported by a copper mesh and is divided into an upper part and a lower part.

[0025] More preferably, the mesh size of the copper mesh is 1 mesh to 60 mesh, for example 6 mesh.

[0026] Preferably, the inert gas is a combination of one or more of argon, helium or nitrogen, such as argon.

[0027] Preferably, the ammonium chloride powder is spread to a thickness of 0.2 cm to 1 cm.

[0028] More preferably, the ammonium chloride powder is spread to a thickness of 0.4 cm-0.6 cm or 0.6 cm-0.8 cm.

[0029] Preferably, the distance between the lithium metal and the ammonium chloride powder is 1 cm-5 cm, more preferably 3 cm-5 cm.

[0030] In this embodiment, the distance between the lithium metal and the ammonium chloride powder refers to the distance from the lower surface of the lithium metal to the upper surface of the ammonium chloride powder.

[0031] Preferably, the temperature of the chemical vapor deposition is 100°C-500°C.

[0032] More preferably, the temperature of the chemical vapor deposition is 300°C-500°C.

[0033] Preferably, the chemical vapor deposition time is 1 h-4 h.

[0034] More preferably, the chemical vapor deposition time is 2h-3h or 3h-4h.

[0035] In this scheme, the time range of chemical vapor deposition can ensure the sufficient formation of the surface interface film without damaging the performance of the lithium metal electrode.

[0036] Preferably, after the chemical vapor deposition step, a flushing step is also included.

[0037] More preferably, in the rinsing step, the rinsing liquid used is one or more of ethylene glycol dimethyl ether, dimethyl carbonate or diethyl carbonate.

[0038] More preferably, in each flushing step, the amount of flushing liquid used is 0.5 mL-2 mL, such as 1 mL-2 mL.

[0039] More preferably, the flushing is performed 1-10 times, such as 3-10 times.

[0040] More preferably, after the rinsing step, a drying step is also included.

[0041] More preferably, the drying time is 5 h-24 h, for example 12 h.

[0042] Preferably, the thickness of the lithium metal is 200 μm-500 μm, preferably 300 μm-400 μm, for example 300 μm.

[0043] Preferably, before the chemical vapor deposition step, a scraping treatment is performed on the side of the lithium metal close to the ammonium chloride powder.

[0044] In this scheme, scraping treatment of the lithium metal side close to the ammonium chloride powder helps to further optimize the state of the lithium metal surface and provide a better basis for the deposition of the surface interface film.

[0045] More preferably, the treatment thickness of the scraping treatment is 10 μm-30 μm, for example, 20 μm-30 μm.

[0046] More preferably, the scraping treatment step is carried out in a glove box.

[0047] Further preferably, the processing equipment for the film scraping treatment is a film scraper.

[0048] More preferably, the scraping treatment step is performed in an inert gas.

[0049] More preferably, the inert gas is argon.

[0050] The present invention also provides a modified lithium metal electrode, which is prepared by the above-mentioned preparation method.

[0051] The present invention also provides a lithium ion battery, which comprises the modified lithium metal electrode as described above.

[0052] The positive and progressive effects of the present invention are:

[0053] (1) The stability of the surface interface film is greatly improved: The present invention forms a surface interface film containing lithium chloride and lithium nitride on the surface of the lithium metal electrode, which significantly improves the electronic insulation and mechanical stability of the electrode. This surface interface film can effectively inhibit the formation and growth of lithium dendrites, reduce the risk of battery short circuit, and thus significantly improve the safety of the battery. In addition, the lithium metal electrode of the present invention has excellent compatibility with ether electrolytes, and the assembled battery exhibits excellent cycle stability and safety.

[0054] (2) Excellent ionic conductivity and electrochemical performance: The low ion diffusion barrier characteristics of the surface interface film of the present invention make the transmission of lithium ions during the charge and discharge process more efficient, thereby improving the ionic conductivity of the battery. This characteristic ensures the stability of the battery during long-term cyclic use, prolongs the service life of the battery and improves its performance.

[0055] (3) Simplification and low cost of preparation method: The chemical vapor deposition technology used in the present invention can not only accurately control the composition of the surface interface film, but also has the characteristics of simplicity and low cost. The raw materials used in the preparation process are easy to obtain, the reaction conditions are easy to control, and large-scale production can be achieved, which has strong potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a cross-sectional SEM image of the modified lithium metal electrode prepared in Example 1.

[0057] Figure 2 Surface SEM image and EDS element distribution map of the modified lithium metal electrode prepared in Example 1.

[0058] Figure 3 The electrochemical performance of the modified lithium metal electrode prepared in Example 1 and the lithium metal electrode prepared in Comparative Example 1 in a Li||Li symmetric battery.

[0059] Figure 4This is the surface SEM image of the lithium metal electrode of Comparative Example 1 used in a Li||Li symmetric battery after 50 cycles.

[0060] Figure 5 The lithium metal electrode prepared in Example 1 was used in a Li||Li symmetric battery. The surface SEM image of the electrode was obtained after 50 cycles. DETAILED DESCRIPTION

[0061] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.

[0062] In the following embodiments, the glove box is from Michelona (Shanghai) Industrial Intelligence Technology Co., Ltd., model Super Pro 750.

[0063] In the following examples, the lithium foil is from Anhui Jinyueguan New Material Technology Co., Ltd., model number is 10377-51-2, and thickness is 300 μm.

[0064] In the following examples, the crucible was sourced from Yixing Wilt Ceramic Technology Co., Ltd. (113×55×25 semicircular boat).

[0065] In the following embodiments, the electric heater is from Heidolph Corporation, model number is 506-11100-05-0.

[0066] In the following examples, the copper mesh was sourced from Anping County Tengde Metal Wire Mesh Products Co., Ltd. (brass wire 6 mesh).

[0067] In the following examples, NH4Cl powder is from Aladdin Chemical Reagent Co., Ltd., model number is 12125-02-9, and purity is 99.5%.

[0068] Example 1

[0069] The modified lithium metal electrode was prepared by the following method:

[0070] S1. In a glove box with an argon atmosphere (H2O≤0.1ppm, O2≤0.1ppm), lithium metal was treated with a scraper with a treatment thickness of 20μm. After treatment, a new metallic luster was observed on the surface of the lithium metal.

[0071] S2. Spread 2g NH4Cl powder evenly on the bottom of the crucible, the thickness of NH4Cl powder spread D is 0.2cm, then place the treated lithium foil on the top of the crucible with a copper mesh as support, the distance H between the lithium foil and the NH4Cl powder is 1cm. Then slowly move the crucible to the electric heater, heat at 100℃ for 1h, naturally cool to room temperature, rinse repeatedly three times with 1mL of electrolyte solvent ethylene glycol dimethyl ether (DME), and dry naturally for 12h to obtain a modified lithium metal electrode.

[0072] Example 2

[0073] Other parameters and preparation methods were the same as those in Example 1, except that the spreading thickness D of the NH4Cl powder was 0.4 cm.

[0074] Example 3

[0075] Other parameters and preparation methods were the same as those in Example 1, except that the spreading thickness D of the NH4Cl powder was 0.6 cm.

[0076] Example 4

[0077] Other parameters and preparation methods were the same as those in Example 1, except that the spreading thickness D of the NH4Cl powder was 0.8 cm.

[0078] Example 5

[0079] Other parameters and preparation methods were the same as those in Example 1, except that the spreading thickness D of the NH4Cl powder was 1.0 cm.

[0080] Example 6

[0081] Other parameters and preparation methods were the same as those in Example 1, and the distance H between the lithium foil and the NH4Cl powder was 3 cm.

[0082] Example 7

[0083] Other parameters and preparation methods were the same as those in Example 1, and the distance H between the lithium foil and the NH4Cl powder was 5 cm.

[0084] Example 8

[0085] Other parameters and preparation methods were the same as those in Example 1. The crucible was slowly moved onto the electric heater and heated at 300° C. for 1 h.

[0086] Example 9

[0087] Other parameters and preparation methods were the same as those in Example 1. The crucible was slowly moved onto the electric heater and heated at 500° C. for 1 h.

[0088] Example 10

[0089] Other parameters and preparation methods were the same as those in Example 1. The crucible was slowly moved onto the electric heater and heated at 300° C. for 2 h.

[0090] Embodiment 11

[0091] Other parameters and preparation methods were the same as those in Example 1. The crucible was slowly moved onto the electric heater and heated at 300° C. for 3 h.

[0092] Example 12

[0093] Other parameters and preparation methods were the same as those in Example 1. The crucible was slowly moved onto the electric heater and heated at 300° C. for 4 h.

[0094] Comparative Example 1

[0095] In a glove box with an argon atmosphere (H2O≤0.1ppm, O2≤0.1ppm), lithium foil was treated with a scraper to a thickness of 20μm. After treatment, a brand new metallic luster could be observed on the surface of the lithium metal.

[0096] Effect Example 1

[0097] The modified lithium metal electrode prepared in Example 1 was observed by SEM, and the results were as follows: Figure 1 and Figure 2 .Depend on Figure 1 It can be seen that the thickness of the surface interface film of the modified lithium metal electrode prepared in Example 1 is 4 μm. Figure 2 From the surface SEM image, it can be seen that the surface interface film of the modified lithium metal electrode prepared in Example 1 is evenly distributed on the surface of the lithium metal.

[0098] Effect Example 2

[0099] The modified lithium metal electrode prepared in Example 1 was subjected to EDS elemental analysis. Figure 2 The distribution diagram of the corresponding chlorine and nitrogen elements in the modified lithium metal electrode fully confirms the generation of LiCl and Li3N. At the same time, it can be intuitively seen that the composite interface film prepared by chemical vapor deposition method, LiCl and Li3N components are uniformly distributed. The EDS spectrum shows that the N and Cl content of the modified lithium metal electrode prepared in Example 1 is 0.7% and 0.5% respectively.

[0100] Effect Example 3

[0101] The modified lithium metal electrode prepared in Example 1 and the lithium metal electrode prepared in Comparative Example 1 were matched with conventional ether electrolyte (DOL:DME=1:1, 1M LiTFSI+0.2M LiNO3) to assemble Li||Li symmetric cells, and their electrochemical performance was tested under the conditions of current density of 0.5mA / cm2 and 2mA / cm2 and limited capacity of 2mAh / cm2. The test results of the samples in Example 1 and Comparative Example 1 are as follows: Figure 3As shown, the gray part is the sample test data of Example 1, and the black part is the sample test data of Comparative Example 1. It can be seen that the Li||Li symmetric battery assembled with the modified lithium metal electrode of Example 1 exhibits low overpotential and better cycle stability, and the Li||Li symmetric battery assembled with the lithium metal electrode that has only been subjected to surface scraping treatment in Comparative Example 1 exhibits unstable potential fluctuations and poor cycle stability.

[0102] After the symmetrical battery was cycled for 50 cycles, the battery was disassembled and the deposition side of the lithium metal electrode of Example 1 and Comparative Example 1 was characterized by SEM. The test results of Example 1 are as follows: Figure 4 As shown, the modified lithium metal electrode exhibits a relatively uniform and flat surface, proving that the composite interface film is uniformly deposited on the surface of the lithium foil. The deposition side of the lithium metal electrode of Examples 2-12 was also characterized by SEM, and the results were consistent with those of Example 1, indicating that the composite interface film was deposited on the surface of the lithium foil. The test results of Comparative Example 1 are shown in Figure 5 As shown, the surface of the lithium metal electrode exhibits large lithium particles and earthworm-like lithium dendrites.

[0103] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A modified lithium metal electrode, characterized in that The modified lithium metal electrode comprises the lithium metal and a surface interface film attached to the surface of the lithium metal; The surface interface film contains lithium chloride and lithium nitride; In the modified lithium metal electrode, the content of Cl element is 0.4%-0.8%, where % is the percentage of the mass of Cl element to the total mass of the modified lithium metal electrode; In the modified lithium metal electrode, the content of N element is 0.4%-0.8%, where % is the percentage of the mass of N element to the total mass of the modified lithium metal electrode.

2. The modified lithium metal electrode according to claim 1, characterized in that The thickness of the surface interface film is 1 μm-100 μm; Preferably, the thickness of the surface interface film is 1 μm-4 μm; And / or, the content of Cl element is 0.7%-0.8%; And / or, the content of the N element is 0.5%-0.6%; And / or, the lithium metal is lithium foil; And / or, the thickness of the lithium metal is 195 μm-499 μm, preferably 295 μm-399 μm, for example 296 μm; And / or, the surface interface film further contains lithium oxide and lithium carbonate.

3. A method for preparing a modified lithium metal electrode, characterized in that: The method comprises the following steps: under the protection of inert gas, placing ammonium chloride powder and lithium metal at the lower part and the upper part of a reaction container respectively without contacting each other, and preparing the reaction by chemical vapor deposition method; The distance between the lithium metal and the ammonium chloride powder is ≤5 cm; The temperature of the chemical vapor deposition is ≥100°C.

4. The method for preparing a modified lithium metal electrode according to claim 3, characterized in that: The reaction container is a crucible; And / or, the reaction vessel is supported by a copper mesh and is divided into an upper part and a lower part; Preferably, the mesh size of the copper mesh is 1 mesh to 60 mesh, for example 6 mesh.

5. The method for preparing a modified lithium metal electrode according to claim 3, characterized in that: The inert gas is a combination of one or more of argon, helium or nitrogen, such as argon; And / or, the thickness of the spread of the ammonium chloride powder is 0.2 cm-1 cm; Preferably, the thickness of the ammonium chloride powder spread is 0.4cm-0.6cm or 0.6cm-0.8cm; and / or, the distance between the lithium metal and the ammonium chloride powder is 1 cm-5 cm, preferably 3 cm-5 cm; And / or, the temperature of the chemical vapor deposition is 100° C.-500° C.; Preferably, the temperature of the chemical vapor deposition is 300°C-500°C; And / or, the chemical vapor deposition time is 1h-4h; Preferably, the chemical vapor deposition time is 2h-3h or 3h-4h.

6. The method for preparing a modified lithium metal electrode according to claim 3, characterized in that: After the chemical vapor deposition step, a rinsing step is also included; Preferably, in the rinsing step, the rinsing liquid used is one or more of ethylene glycol dimethyl ether, dimethyl carbonate or diethyl carbonate; Preferably, in each flushing step, the amount of flushing liquid used is 0.5 mL-2 mL, for example, 1 mL-2 mL; Preferably, the number of flushing is 1-10 times, for example 3-10 times; Preferably, after the rinsing step, a drying step is also included; More preferably, the drying time is 5h-24h, for example 12h.

7. The method for preparing a modified lithium metal electrode according to claim 3, characterized in that: The thickness of the lithium metal is 200 μm-500 μm, preferably 300 μm-400 μm, for example 300 μm; and / or, before the chemical vapor deposition step, performing a scraping treatment on a side of the lithium metal close to the ammonium chloride powder; Preferably, the scraping treatment has a treatment thickness of 10 μm-30 μm, for example 20 μm-30 μm; Preferably, the film scraping treatment step is performed in a glove box; Preferably, the processing equipment for the film scraping process is a film scraper; Preferably, the scraping treatment step is performed in an inert gas; More preferably, the inert gas is argon.

8. A modified lithium metal electrode, characterized in that The modified lithium metal electrode is prepared by the preparation method described in any one of claims 3-7.

9. Use of the modified lithium metal electrode according to any one of claims 1 to 2 or claim 8 in a lithium ion battery.

10. A lithium ion battery, characterized in that: It comprises the modified lithium metal electrode according to any one of claims 1 to 2 or claim 8.

Citation Information

Patent Citations

  • Anode material for lithium metal batteries

    CN106803580A

  • Preparation and application of lithium metal anode with composite film

    CN110190243A

  • Modifier cembrinium chloride for electrolyte as well as modification method and application of modifier cembrinium chloride

    CN113707937A

  • Lithium metal negative electrode and preparation method and application thereof

    CN113903889A

  • Negative electrode, preparation method thereof and lithium secondary battery

    CN114597515A